Environment-friendly preparation of porous graphite-phase polymeric carbon nitride using calcium carbonate as templates, and enhanced photoelectrochemical activity1. Issue 9 (7th March 2015) - Wang, Jianhai; Zhang, Cheng; Shen, Yanfei; Zhou, Zhixin; Yu, Jiachao; Li, Ying; Wei, Wei; Liu, Songqin; Zhang, Yuanjian
<x xml:space="preserve">Abstract</x> Superior to silica nanoparticles, the easily accessible and removable CaCO3 particles produced porous carbon nitride with photocurrents 7.5-times that of the bulk one.